2021
DOI: 10.1055/a-1471-3786
|View full text |Cite
|
Sign up to set email alerts
|

Prädiktoren der Legalbewährung nach forensischer Suchtbehandlung – Zweiter Teil einer Übersichtsarbeit zu Erfolgsdeterminanten einer Unterbringung gemäß § 64 StGB

Abstract: Zusammenfassung Hintergrund Ehe eine forensische Suchtbehandlung gemäß § 64 StGB gerichtlich angeordnet werden kann, ist eine Erfolgsprognose zu stellen und zu bejahen. Der Suche nach entsprechenden Prädiktoren für eine „hinreichend konkrete“ Erfolgsaussicht widmeten sich in den vergangenen Jahren einige Studien. Dabei stellt die Legalbewährung nach Entlassung das gesetzlich vorgesehene Erfolgskriterium forensischer Suchtbehandlung dar. Zielsetzung Als zweiter Teil einer zweiteiligen Gesamtschau zu Erfolgsdete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
1
4
0
2
Order By: Relevance
“…Butz ( 28 ) found that rates of reconviction were significantly positively correlated with substance-related index offences, and that having no prior offence was linked with lower rates of reconviction. Querengässer et al ( 27 ) found a range of offences positively correlated with reconviction rates with the strength of the relationship in the following descending order: property crime, assault, an ‘other’ category including traffic offences, arson, ‘other’ violent crimes including attempted offences, homicide, offences against the Betäubungsmittelgesetz (BtMG; Narcotics Law), and sexual offences. Koch ( 30 ) reported no significant association between index offence type and reconviction, a finding replicated in Bezzel ( 32 ) study of reoffending.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Butz ( 28 ) found that rates of reconviction were significantly positively correlated with substance-related index offences, and that having no prior offence was linked with lower rates of reconviction. Querengässer et al ( 27 ) found a range of offences positively correlated with reconviction rates with the strength of the relationship in the following descending order: property crime, assault, an ‘other’ category including traffic offences, arson, ‘other’ violent crimes including attempted offences, homicide, offences against the Betäubungsmittelgesetz (BtMG; Narcotics Law), and sexual offences. Koch ( 30 ) reported no significant association between index offence type and reconviction, a finding replicated in Bezzel ( 32 ) study of reoffending.…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analysis would not have produced meaningful insights given the number of variables measured in the literature and heterogeneous operationalisations [for example, number of past criminal offences was variously measured as: low, medium, and high severity in Gericke and Kallert ( 26 ); total number of officially recorded convictions in, for example, Querengässer et al ( 27 ); and number of self-reported offences in Butz ( 28 )]. Therefore, we have chosen to present the findings as a narrative synthesis in line with the general framework proposed by the Centre for Reviews and Dissemination ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prädiktoren einer positiven Legalbewährung waren das Vorhandensein lebenspraktischer, sozialer und motivationaler Ressourcen, weiterhin spielen Delinquenzfaktoren wie eine hohe Vorstrafenbelastung, Vorbehandlungen in der Forensik und das Anlassdelikt (eher ungünstig: BtMG-Delikt; eher günstig: Körperverletzungs-, Straßenverkehrs-, Brandstiftungs-, Sexualdelikt) eine Rolle. Insgesamt wurde jedoch auch darauf hingewiesen, dass die Erkenntnisse nur eine bedingte Vorhersage ermöglichen und nicht zu verallgemeinern sind, da sie über eine Zeitspanne von 20 Jahren in mehreren Bundesländern von verschiedenen Arbeitsgruppen bei unterschiedlichen Populationen mit variierenden Methoden erhoben wurden 10 .…”
Section: Introductionunclassified
“…eines primär kriminellen Verhaltens mit sekundär einsetzendem Substanzkonsum. Eine umfassende Übersicht über die aktuelle Studienlage hinsichtlich möglicher Erfolgsdeterminanten einer forensischen Suchtbehandlung bieten zwei aktuelle Arbeiten von Querengässer und Baur 10 11 . Patienten mit einer Kombination aus frühem Beginn des kriminellen Verhaltens, problematischen Indikatoren für soziale Integration (beruflicher Werdegang, Bildungsgrad etc.)…”
Section: Introductionunclassified